Association of Atrial Fibrillation Without Cardiovascular Comorbidities and Stroke Risk: From the REGARDS Study. Issue 12 (16th June 2020) - Singleton, Matthew J.; Imtiaz‐Ahmad, Muhammad; Kamel, Hooman; O'Neal, Wesley T.; Judd, Suzanne E.; Howard, Virginia J.; Howard, George; Soliman, Elsayed Z.; Bhave, Prashant D.
Abstract : Background: Atrial fibrillation (AF) is associated with a 5‐fold increased stroke risk. While most patients with AF warrant anticoagulation, optimal treatment remains uncertain for patients with AF without cardiovascular comorbidities because the risk of stroke in this population has not been well‐characterized. Methods and Results: Participants (N=28 253; 55% women, mean age 64.6±9.4 years), from the REGARDS (Reasons for Geographic and Racial Differences in Stroke) study (2003–present) were classified into 1 of 4 groups based on the presence or absence of AF and the presence or absence of cardiovascular comorbidities. Cox proportional hazards analysis was used to compare the risk of stroke between groups. During 244 560 person‐years of follow‐up (median 8.7 years), 1206 strokes occurred. Compared with patients with neither AF nor cardiovascular comorbidities, we did not find an increased stroke risk (hazard ratio [HR], 1.23; 95% CI, 0.62–2.18 [ P =0.511]) among participants with AF alone. Participants without AF but with cardiovascular comorbidities had both an elevated stroke risk (HR, 1.77; 95% CI, 1.48–2.18 [ P <0.0001]) and an increased risk of cardioembolic stroke (HR, 2.34; 95% CI, 1.48–3.90 [ P =0.0002]). Conclusions: In this large cohort of participants with AF without cardiovascular comorbidities, we found that AF itself, without cardiovascular comorbidities, did not confer increased risk of stroke. Cardiovascular comorbidities, however, were associated with an increased risk of both stroke of any type and cardioembolic stroke, even in the absence of AF.